Effect of Bacterial Cellulose (BC) Formation on Various Substrate Variations and Combinations - Siti Assyifa Liany; Wilda Syafira; Adelia Putri; Anis Uswatun Khasanah (Fakultas Biologi Universitas Gadjah Mada, 2022)
Cellulose is one of the most abundant polymers on the earth's surface and is often used as the main raw material in various industries. Bacterial Cellulose (BC) is an organic compound produced by certain types of bacteria with various variations and combinations of substrates, including coconut water, rice soaking water, tomatoes, and a mixture of tomato-rice water, coconut-tomato water, and coconut water-rice water. This study aims to determine the optimization of BC formation in various variations and combinations of substrates with organoleptic and physical tests on each sample. This study used experimental methods on each substrate and analyzed descriptively qualitatively. The formula for making BC was 50 mL of each substrate, 5 grams of sugar, 2 grams of ZA (ammonium sulfate), 2 grams of glacial acetic acid, and 2 mL of starter (Acetobacter xylinum). The results of this study obtained organoleptic BC by 90% of panelists liked it, and 10% of panelists disliked it. Meanwhile, the best optimization of BC production obtained the highest thickness and yield on the coconut-rice water substrate treatment of 2.3 cm and 80% yield, the highest water content on the coconut water, coconut-tomato water, and coconut-rice water substrate treatments, respectively, each of 97% and the highest fiber content in rice water, tomato water, and tomato-rice water substrates were 3% each.